Mulla Sadra and the Necessity of Contrast in the Foundation of Metaphysics (The Faith-Mystic Taste in the Scale of Human Transcendental Reason) - Mahdi Sadafi (حکمت اسرا, 2025)
The following article aims to criticize the principles of the Dawani “Divine Taste” and the mystical “Oneness of existence” of Ibn Turki with a view to the principles of Sadr’i transcendental wisdom. It seems that Sadr’i’s fundamental objection to these principles has not been properly understood, in such a way that Haji Sabzevari and Allama Hassanzadeh Amoli, two Sadr’i philosophers, intend to correct and prepare the Divine Taste and extend it to the point of proving the view of the mystics, although Allama Javadi Amoli places the “Divine Taste” in the line of intuitive mysticism and considers it in the theoretical field of the type of “psychological certainty”. The question arises as to what fundamental problem Mulla Sadra saw in the taste-mystical views of the Mahowīs’ originality that he turned away from and repeatedly warned about?Our task in the present article is to examine the foundation of metaphysics. This foundation has always reminded itself from the beginning that the simple unit separated and isolated from the multiplicity deprives it of truth, emptiness and provides the ground for the emergence of nihilism. Hence, philosophers in different eras have warned about the dialectic of the one and the many or, in other words, the objectivity of unity and multiplicity, and have perhaps called it the most fundamental principle of philosophy, and the lack of attention to this principle traps metaphysics in the trap of a rigid and unresponsive foundation (mono-logue) that is indifferent to human life.